Clean hands for healthy children - Clark, Mary P.; Peters, Paula; Grover, Phyllis (My University, 1994)
Clean hands for healthy children is the first in a five part program on Safe Food for Children: A series of lessons for parents and child care providers.
L892_1994-11
Keywords: L892; Home and Family; Health and Safety; L